Citizen journalism under pressure: the case of Indonesia, Malaysia and the Philippines - Prawira, Indra; Mahamed, Mastura (SAGE Publications, 2025)
Citizen journalism was perceived to be a beacon of hope for democracy throughout countries in Southeast Asia. Nonetheless, recnt developments indicate citizen journalism in the region is being challenged. This research exploits Pierre Bourdieu’s field theory to understand contemporary Southeast Asian citizen journalism. The data was collected by way of semi-structured interviews conducted with thirty people participating in citizen journalism from Indonesia, Malaysia, and the Philippines. The findings demonstrate prevalent economic, political, and cultural pressures in these countries, with political factors exerting the most pressure on the rise of citizen journalism. All three nations experience political pressure via regulations, with the Philippines being subjected to the most pressure due to extrajudicial killings and the intimidation of journalists. Owing to financial constraints, citizen journalism acts as a venue for mainstream media to obtain free content from citizen journalists. Citizen journalists in Indonesia earn significant incomes, although professional journalists covertly adopt their posts. Cultural pressure capital is exhibited when journalists apply ethical journalism to citizen journalists by means of training. Moreover, in the Philippines, citizen journalism is commonly positioned by government-supporting politicians to disinform. This study delivers an extensive and comparative overview, strengthening the case to update field theory.